TikToker Political Campaign in the 2024 Presidential and Vice Presidential Election - Dwiana, Ressi; Barus, Rehia (Talenta Publisher, 2024)
This article discusses the campaign style of supporters of presidential candidates (capres) and vice presidential candidates (cawapres) who are contesting in the 2024 General Election (Pemilu). The research focuses on the five presidential and cawapres debates held. During the debate period, supporters of the presidential and vice presidential candidates carried out amplification by uploading video clips of the debate on TikTok. This research uses a descriptive qualitative approach. Data was collected during the presidential and vice presidential debate period. The research results show that TikTokers creatively use typical TikTok features to highlight the advantages of the presidential candidate pairs they support. However, on the other hand, the TikTokers' posts were not equipped with the data presented by the candidates during the debate. With this TikToker campaign model, even though it is successful in terms of political marketing, it lacks political education. Keyword: political campaign, 2024 Election, TikTok